2018
DOI: 10.1055/s-0038-1666860
|View full text |Cite
|
Sign up to set email alerts
|

Inflammasome, T Lymphocytes and Innate-Adaptive Immunity Crosstalk: Role in Cardiovascular Disease and Therapeutic Perspectives

Abstract: Over the past few decades, lot of evidences have shown atherosclerosis as a chronic progressive disease with an exquisite inflammatory feature. More recently, the role of innate immune response in the onset and progression of coronary artery disease (CAD) and an adaptive immunity imbalance, mostly involving T cell sub-sets, have been documented. Therefore, like in many other inflammatory and autoimmune disorders, an altered innate-adaptive immunity crosstalk could represent the key of the inflammatory burden l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
20
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 152 publications
(156 reference statements)
0
20
0
Order By: Relevance
“…The pathophysiology of ACS is strictly related to an outburst of inflammatory (Biasucci et al, 2017) and immune-mediated response (Crea and Liuzzo, 2013), taking over the concept of the atheroma as a mere lipid-driven lesion (Soehnlein and Libby, 2021). Differences in innate and adaptive immune system have been described in ACS patients (Liuzzo et al, 2007(Liuzzo et al, , 2020Flego et al, 2016;Leers et al, 2017;Pedicino et al, 2018a;Leistner et al, 2020). Starting from PBMCs as source material, our group documented an altered hyaluronan metabolism in NSTE-ACS patients presenting with plaque erosion (Pedicino et al, 2018b), further confirmed by later investigations on platelets and monocyte-platelet interaction (Vinci et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The pathophysiology of ACS is strictly related to an outburst of inflammatory (Biasucci et al, 2017) and immune-mediated response (Crea and Liuzzo, 2013), taking over the concept of the atheroma as a mere lipid-driven lesion (Soehnlein and Libby, 2021). Differences in innate and adaptive immune system have been described in ACS patients (Liuzzo et al, 2007(Liuzzo et al, , 2020Flego et al, 2016;Leers et al, 2017;Pedicino et al, 2018a;Leistner et al, 2020). Starting from PBMCs as source material, our group documented an altered hyaluronan metabolism in NSTE-ACS patients presenting with plaque erosion (Pedicino et al, 2018b), further confirmed by later investigations on platelets and monocyte-platelet interaction (Vinci et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation plays an important role in the occurrence and development of atherosclerotic cardiovascular disease and is related to the poor prognosis of ACS ( 5 , 6 , 22 ). NLR and PLR are inflammatory indicators that have been used to assess the levels of inflammation in cardiovascular diseases in recent years ( 15 , 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it has been shown that the tryptophan metabolite 3-hydroxyanthranilic acid has immune regulatory properties that can be used to decrease atherosclerosis in mice by regulating T-cell-dependent inflammation and lowering plasma lipids. 12 Second, which patients might benefit from an antiinflammatory treatment? Although a large body of evidence suggests that CRP is a good biomarker for the identification of patients with residual inflammatory risk and blood cell count, as suggested by the study of Zhao et al, 5 there might be another interesting biomarker of risk in this setting: T-cell perturbation seems to identify patients with ACS at high risk of major coronary events even better than high-sensitivity CRP.…”
mentioning
confidence: 99%
“…In addition, it has been shown that the tryptophan metabolite 3-hydroxyanthranilic acid has immune regulatory properties that can be used to decrease atherosclerosis in mice by regulating T-cell-dependent inflammation and lowering plasma lipids. 12…”
mentioning
confidence: 99%